Death begets a new beginning. Issue 1 (13th October 2017) - Bosurgi, Lidia; Hughes, Lindsey D.; Rothlin, Carla V.; Ghosh, Sourav
Summary: Cell death is a perpetual feature of tissue microenvironments; each day under homeostatic conditions, billions of cells die and must be swiftly cleared by phagocytes. However, cell death is not limited to this natural turnover—apoptotic cell death can be induced by infection, inflammation, or severe tissue injury. Phagocytosis of apoptotic cells is thus coupled to specific functions, from the induction of growth factors that can stimulate the replacement of dead cells to the promotion of tissue repair or tissue remodeling in the affected site. In this review, we outline the mechanisms by which phagocytes sense apoptotic cell death and discuss how phagocytosis is integrated with environmental cues to drive appropriate responses.